Trade Union Participation and Influence at Norwegian Workplaces During the Pandemic - Trygstad, Sissel C.; Andersen, Rolf K.; Ødegård, Anne Mette (Nordic Journal of Working Life Studies, 2023)
A central feature of the Nordic model of labor relations, namely, the collaboration between social parties at the workplace, has proven to be particularly effective during crises. This is the backdrop for our study of the experiences from Trade Union Representatives (TU-reps) during the corona pandemic. With a survey aimed at TU-reps from the Norwegian Confederation of Trade Unions (LO), which represents just under half of the total unionized employees, we asked how the pandemic affected their participation and influence at the workplaces. Referring to the pandemic as a game changer, we discuss signs of change in TU-reps’ possibilities for participation and influence under such difficult circumstances. According to theTU-reps, interaction between the social parties intensified during the pandemic. Formal participation between the parties stands out to be crucial for enabling dialog and can therefore be labeled as the backbone of the Nordic model in times of crisis.